The Role of Digital Leadership Mediated by Digital Skill in Improving Organizational Performance - Tulungen, Evans E.W.; Tewal, Bernhard; Pandowo, Merinda (Universitas Syiah Kuala, 2022)
Objective-The main objective is to examine the role of digital leadership mediated by digital skill in improving organizational performance in line with digital transformation efforts within the General Election Commission of North Sulawesi.Design/methodology-The sample used in this study amounted to 78 people who are elements of the commissioner and secretariat of the General Election Commission of North Sulawesi Province. Testing the relationship between variables and hypotheses was carried out using the Structural Equation Modeling (SEM) technique.Results-Based on the results of hypothesis testing, it can be concluded that Digital Leadership has a significant effect on Organization Performance and Digital Skills. Meanwhile, Digital Skill has a positive effect on Organizational Performance but does not have a significant effect. The indirect relationship between Digital Leadership and Organizational Performance through Digital Skills does not have a significant effect.Research limitations/implications-This study concludes that the role of digital leadership has a major influence on improving organizational performance in the era of digital transformation. The era of technology 4.0 requires leaders to develop their digital skills in utilizing technology to face the development of information technology in organizations.Novelty/Originality-The originality of this research lies in the object of research where previous studies have only analyzed the digital transformation process in the private sector but the public sector namely the government has not been carried out.